Does the application of autologous injectable Platelet-Rich Fibrin (i-PRF) affect the patient's daily performance during the retraction of upper canines? A single-centre randomized split-mouth controlled trial - Zeitounlouian, Talar; Haddad, Rania; Brad, Bassel; Ballouk, Muhammed Al-Huda; Fudalej, Piotr (BMC oral health, 2023)
BACKGROUND: Previous studies have assessed different aspects concerning the applications of i-PRF in the oral cavity. However, nothing is known regarding patients' perceptions of the injection of autologous platelet-rich fibrin (i-PRF). OBJECTIVES: To investigate patients' perceptions after injecting platelet-rich fibrin (i-PRF) in the course of retracting upper canines. METHODS: Twenty-one patients, whose treatments required extractions of both upper first premolars, were recruited. Extraction side was randomly allocated to the intervention or control sides. After the alignment phase, i-PRF was injected twice with a one-month interval on the buccal and palatal aspects of the extraction sites (intervention side). Patients' perceptions were evaluated with two questionnaires: the first was used to assess the level of pain, discomfort, swelling, eating and swallowing difficulties as well as jaw movement restriction after 1 h (T1), 2 h (T2), 6 h (T3), 24 h (T4) and 48 h (T5) of the second injection; the second questionnaire was used to assess the acceptance of the i-PRF injection and overall satisfaction with this technique at the end of canine retraction phase. Visual Analogue Scale (VAS) was adopted for this purpose. Wilcoxon Signed Rank Test was used to compare between both sides at all time points while Friedman's Test was the selected test for detecting variables' changes over time. Post-hoc Wilcoxon Matched-Pairs Signed-Rank Tests were applied when any of the results were significant. As to the multiplicity of tests, Bonferroni Correction was implemented. RESULTS: Pain and swelling levels were significantly higher on the experimental compared to the control sides at T1, T2, and T3 (P < 0.05), whereas they declined sharply and went back to almost normal values at T4 (after 24 h). At T5 they were 0. Discomfort and difficulty in mastication on intervention sides were significant only at T1 and T2. Pain, swelling, and chewing difficulties were significant (P < 0.001) during the 4 assessed time points. The increase was insignificant regarding swallowing difficulties and jaw movement limitations at all time intervals. CONCLUSIONS: Injecting autologous (i-PRF) during orthodontic canine retraction is a well-perceived and well-tolerated method due to the limited discomfort which significantly diminishes 24 h afterwards. TRIAL'S REGISTRATION: ClinicalTrials.gov (Identifier Number: NCT03399422. 16/01/2018).
Keywords: Mouth; Quality of Life (QoL); pooperační bolest; Pain, Postoperative; Maxillary canine retraction; lidé; fibrin bohatý na krevní destičky; Injectable Platelet-Rich Fibrin (i-PRF); Dental Care; Tooth Extraction; extrakce zubů; Visual Analogue Scale (VAS); Platelet-Rich Fibrin; stomatologická péče; ústa; Patient-Reported Outcome Measures (PROMs); Humans